Compound Heterozygosity of the GPIbα Gene Associated with Bernard-Soulier Syndrome - González-Manchón, Consuelo; Larrucea, Susana; Pastor, Angela L.; Butta, Nora; Arias-Salgado, Elena G.; Ayuso, Matilde S.; Parrilla, Roberto (Thrombosis and Haemostasis, 2001)
We report the molecular genetic analysis of the Bernard-Soulier syndrome (BSS) phenotype in two related patients showing absence of glycoprotein (GP) Ibα and detectable amounts of GPIX on the platelet surface, and a truncated form of GPIbα in solubilized platelets and plasma. They both were compound heterozygotes for the GPIbα gene: a maternal allele with a T insertion at position 1418 causing a translational frameshift and premature polypeptide termination, and a paternal allele with a T715A substitution changing Cys209 to Ser. Heterozygotes for either one of these mutations were asymptomatic. Transient transfection of cells coexpressing GPIbβ and GPIX failed to detect surface expression of the GPIbα mutants. Cells transfected with [1418insT]GPIbα-cDNA showed a truncated protein of the predicted size in both cell lysate and conditioned medium, indicating the inability of the mutant protein to anchor the plasma membrane. In contrast, transfection of [T715A]GPIbα-cDNA yield a mutated protein barely detectable in the cell lysate and absent in the medium, indicating that the loss of Cys209 renders GPIbα more vulnerable to proteolysis and unable to undergo the normal secretory pathway. Our findings indicate that the additive effects of both mutations are responsible for the BSS phenotype of the patients.
Keywords: GPIb-IX; Bernard-Soulier syndrome; platelets